RE-CONCEPTUALIZING L2 WRITING REVISION STRATEGIES FROM AN ECOLOGICAL PERSPECTIVE: AN INTERVIEW BASED INQUIRY - Masakazu Mishima (English Review: Journal of English Education, 2019)
This study examines an ESL writer’s revision activity in composing an argumentative essay from an ecological perspective. The study aimed to explore how sociomaterial conditions present in the pedagogical context lead to the writer’s use of revision strategies in responding to instructor feedback. By using an interview-based case study approach, data were collected from one ESL writer and instructor in an ESL freshman composition class at a large public university in the US. Based on the analysis of field-notes, transcripts from interviews and writing conferences, and various cultural artifacts, the study found that the writer’s goal-oriented agency foregrounded his engagement with instructor feedback, which narrowed down the problem space perceived to be important by the writer to achieve his goal in writing. The writer’s selective attention to the specific writing issues to be attended in his revision attempt provided an essential perceptual pretext for the concoctions of several sociomaterially-afforded revision strategies. The study also found that sociomaterial interactions inherent within one strategy use conditioned the emergence of another strategy while showcasing that the writer’s strategy use could be emergent and generative in nature. Based on the findings, the study discusses the emergence of the revision strategies as a result of collective interplay of student agency and student-perceived sociomaterial affordances in the writer’s attempt to establish sociocognitive alignment with the instructor’s expectations delivered through feedback. Implications for ecologically-oriented L2 revision strategy research are discussed.